1985
DOI: 10.1159/000183433
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Intraperitoneal Cefotaxime Treatment of Peritonitis in Patients on Continous Ambulatory Peritoneal Dialysis

Abstract: The pharmacokinetics of intraperitoneal cefotaxime as the sole therapy in patients on continous ambulatory peritoneal dialysis with peritonitis have been examined. The mean plasma concentrations achieved following 1 h of peritoneal instillation of 500 mg of cefotaximine were 5.0 ± 1.6 μg ml-1. The average plasma concentration over 24 h was 6.9 ± 0.4 μg ml-1 and was no different from that found following a further 9-11 days of successful treatment of the peritonitis. However, the mean dial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Patients with ESRD undergoing hemodialysis are quite different from those undergoing CAPD since in the former a highly dialyzable drug is removed extensively during hemodialysis, and after completion of the procedure, a supplemental dose may be necessary to reestablish therapeutic drug levels, whereas in patients on CAPD, a continuous exchange of drug may occur throughout the 24-h period and the drug excretion via this route would depend on the rate of transperitoneal movement and the number of exchanges per day. Results of previous investigations (1,4,11,17) with single drugs showed that some drugs such as gentamicin (22), tobramycin ( (13) are poorly eliminated by PD although they are rapidly absorbed when given i.p. However, only 3 to 10% of the highly dialyzable drugs (e.g., ceftizoxime) are eliminated by this route (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with ESRD undergoing hemodialysis are quite different from those undergoing CAPD since in the former a highly dialyzable drug is removed extensively during hemodialysis, and after completion of the procedure, a supplemental dose may be necessary to reestablish therapeutic drug levels, whereas in patients on CAPD, a continuous exchange of drug may occur throughout the 24-h period and the drug excretion via this route would depend on the rate of transperitoneal movement and the number of exchanges per day. Results of previous investigations (1,4,11,17) with single drugs showed that some drugs such as gentamicin (22), tobramycin ( (13) are poorly eliminated by PD although they are rapidly absorbed when given i.p. However, only 3 to 10% of the highly dialyzable drugs (e.g., ceftizoxime) are eliminated by this route (9,10).…”
Section: Discussionmentioning
confidence: 99%